2010
DOI: 10.1177/1077800410372606
|View full text |Cite
|
Sign up to set email alerts
|

Using Humor to Move Away From Abjection

Abstract: The absence of discourses on death makes it difficult for those dealing with loss to communicate about their experiences. Our emotions vary even more when we see the corpse of a loved one at the funeral. It is overwhelming; a family member is gone, death, and you are faced with your own mortality, abjection. The author recently experienced the death of her grandmother and confronted her own abjection. The author writes this story as a third way of knowing. The author wants to share her experience by offering a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…One described the joking that is done by attendees at African funerals and African funerals where comedians were increasingly appearing (Pype, 2015 ). Marmo’s ( 2010 ) article indicated that humor was often used by grieving family members; with humor easing tensions, reducing stress, and opening lines of communication among family members who are coping with a death. Moreover, in that paper, humor was said to help initiate a realization of one’s own death in the future (Marmo, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One described the joking that is done by attendees at African funerals and African funerals where comedians were increasingly appearing (Pype, 2015 ). Marmo’s ( 2010 ) article indicated that humor was often used by grieving family members; with humor easing tensions, reducing stress, and opening lines of communication among family members who are coping with a death. Moreover, in that paper, humor was said to help initiate a realization of one’s own death in the future (Marmo, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…Marmo’s ( 2010 ) article indicated that humor was often used by grieving family members; with humor easing tensions, reducing stress, and opening lines of communication among family members who are coping with a death. Moreover, in that paper, humor was said to help initiate a realization of one’s own death in the future (Marmo, 2010 ). Similarly, a report about the House of Being, a Holocaust-survivor combined geriatric center and memorial museum in Israel, discussed the common use of humor and the importance of humor for Holocaust descendants (Kidron, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…O humor tem por objetivo primeiro divertir, mas também realiza diversas outras funções (Roth & Vivona, 2010;Schnurr, 2008;Holmes, 2007;Lynch & Schaefer, 2009;Heiss & Carmack, 2011;Kidd, Miller, Boyd, & Cardeña, 2009 (Romero & Cruthirds, 2006;Greatbatch & Clark, 2003;Kidd, Miller, Boyd, & Cardeña, 2009;Santos, 2003), Estresse (Romero & Cruthirds, 2006;Heiss & Carmack, 2011;Greatbatch & Clark, 2003;Marmo, 2010;Duarte & Duarte, 2009, Santos, 2003, Comunicação (Romero & Cruthirds, 2006;Marmo, 2010;Santos, 2003), Criatividade (Romero & Cruthirds, 2006, Santos, 2003, Cultura organizacional (Romero & Cruthirds, 2006;Holmes, 2009;Santos, 2003) e Liderança (Romero & Cruthirds, 2006;Holmes, 2009). …”
Section: O Papel Do Humor Nas Organizaçõesunclassified